“MY BROTHER SAYS GIRLS DON’T DO MATHEMATICS”: GIRLS’ EDUCATIONAL EXPERIENCES AND SECONDARY SCHOOL PROGRAMME CHOICES IN GHANA - Agbley, G. K. (UDS International Journal of Development, 2016)
Education has a central role in improving the life-chances of an individual and in the benefit that accrues to society from an educated populace. Formal education is viewed as an opportunity for working class children to advance socially while the widening of access to secondary and tertiary education is as a step towards a meritocratic society. The 2013 Ghana Report of the Millennium Development Goals (MDGs) shows that steady progress has been made towards attainment of equal access of girls and boys to education. Meanwhile gender disparity within programme choices continues to exist at the secondary school level. The paper asks the fundamental question why girls continue to dominate in Home Economics departments while boys are inclined to offer mathematics and technical/scientific subjects in secondary schools. The focus is on factors beyond the school. The paper draws on primary fieldwork conducted through a comparative study of 15-23 year olds in Obuasi, Ghana and secondary data from three post-basic institutions. The research used qualitative data collection tools and analysed the data using Atlas-ti. Findings show that girl’s programmes of study are not influenced by school factors alone, but also by significant male relations towards programmes that are perceived to be less maths inclined. In order to overcome such patriarchal tendencies three capability spaces are identified as significant in capturing girls’ agency when selecting secondary school programme of study. Keywords: Agency, Capability, Gendered Experience, Programme of Study, Target-Driven Discourse